The Fundamental Paradox in the Grief Literature: A Critical Reflection - Breen, L.; O'Connor, Moira (Baywood Publishing Company Inc, 2007)
A key theme in the bereavement literature is the recognition that every grief experience is unique and dependent on many variables, such as the circumstances of the death, characteristics of the bereaved individual, their relationship with the deceased, the provision and availability of support, and a myriad of sociocultural factors. Concurrently, there are corresponding efforts to define "normal" grief and delineate it from "complicated" grief experiences. The discord between these two potentially opposing statements remains a paradox evident within the three major tensions within the thanatological literature—the dominance of grief theories, the medicalization of grief, and the efficacy of grief interventions. Three recommendations for moving beyond the paradox are discussed—the provision of improved grief education for service providers, the bereaved, and the wider community; the conduct of research that emphasizes the context of grief and is relevant to service provision; and the examination of current grief interventions.